Pancasila Resilience in Facing the Digitalization Era in the Millennial Generation - Dodoh Siti Saadah; Hilda Nur Fadhilah; Neng Rika Susanti; Rinrin Nurjanah; Silna Rahmatika; Ahmad Fuadin (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Pancasila as the nation's view of life is a form of crystallization of cultural values, social behavior of the people, customs that serve as guidelines in the life of the nation and state. Today, Indonesia faces various challenges in the digital era. The digital era is the point of progress of human civilization, especially in the development of Science and Technology (IPTEK), one of which is marked by the emergence of the existence of social media. Social media certainly makes it easy for its users, through social media we can share information and communicate without being limited by space and time. However, like the two sides of a coin, we cannot deny that social media also has a negative influence, especially on millennials. If we look at the existing reality, of course we realize that this social media causes norms, values, manners, customs which are truly the identity of the Indonesian nation which gradually fade away. Thus, in facing the current rapid flow of digitalization, it is necessary to have Pancasila resilience as a form of maintaining Pancasila values so that they live on in the soul of the Indonesian nation.